The predictive role of E/e′ on ischemic stroke and atrial fibrillation in Japanese patients without atrial fibrillation. Issue 1 (July 2018) - Arai, Riku; Suzuki, Shinya; Semba, Hiroaki; Arita, Takuto; Yagi, Naoharu; Otsuka, Takayuki; Sagara, Koichi; Sasaki, Kenichi; Kano, Hiroto; Matsuno, Shunsuke; Kato, Yuko; Uejima, Tokuhisa; et al.
Highlights: E / e ′ was associated with various atherothrombotic risk factors. Accordingly, E / e ′ was independently associated with ischemic stroke events. Moreover, E / e ′ was significantly associated with new appearance of atrial fibrillation (AF). However, its association with AF was attenuated when adjusted for left atrial dimension. Abstract: Background: The predictive role of E / e ′ on ischemic stroke (IS) and atrial fibrillation (AF) in Japanese patients without AF are unclear. Methods and results: Shinken database includes all the new patients visiting the Cardiovascular Institute Hospital in Tokyo, Japan. E / e ′ has been routinely measured since 2007. Patients without AF for whom E / e ′ was measured at the initial visit between 2007 and 2014 ( n  = 11 477, mean age 57.2 years old, men 59.5%) were divided into E / e ′ tertiles (<8.04, 8.04–11.00, >11.00). During the mean follow-up period of 1.8 years, 58 IS and 140 new appearances of AF were observed. High E / e ′ tertile was associated with more prevalence of atherothrombotic risks. The cumulative incidence of IS events and new appearance of AF at 6 years in low, middle, and high E / e ′ tertiles were 0.5%, 1.4%, and 3.0%/year (log-rank test, p  < 0.001), and 2.5%, 2.9%, and 4.2%/year (log-rank test, p  = 0.007), respectively. In multivariate analysis, high E / e ′ tertile was independently associated with IS (HR, 2.857, 95%CI 1.257–6.495, p  = 0.012). Although high E / e ′ tertile was independently associated with new appearance of AF when adjusted for coexistence of atherothrombotic risk factors (HR, 1.694, 95%CI, 1.097–2.616, p  = 0.017), the association was attenuated after adjustment for left atrial dimension. Conclusions: E / e ′ was significantly associated with incidence of IS and new appearance of AF in non-AF patients.